The Effect of Growth Monitoring and Promotion (GMP) Program Counseling on Mothers’ Behavior in Monitoring the Growth of Malnourished Children Under Two Years Old - Wulansari; Sutarto; Betta Kurniawan; Suharmanto; Khairun Nisa Berawi (Jurnal Ilmiah STIKES Yarsi Mataram, 2026)
Malnutrition in children under two years of age remains a public health problem that affects child growth and development. One of the interventions implemented to address this issue is the Growth Monitoring and Promotion (GMP) program accompanied by nutrition counseling for mothers. This study aimed to analyze the effect of GMP program counseling on maternal behavior in monitoring the growth of malnourished under-two children in the working area of the Margototo Public Health Center, East Lampung Regency. This study used a quantitative approach with a one-group pretest-posttest design. The sample consisted of 30 mothers who had malnourished under-two children, selected using a total sampling technique. Quantitative data were analyzed using the paired t-test. The results showed a significant improvement in mothers’ knowledge, attitudes, practices, and behaviors after GMP counseling (p < 0.001). In addition, there was an increase in children’s body weight after the intervention. In conclusion, GMP counseling was effective in improving maternal behavior in monitoring the growth of malnourished under-two children and supporting weight gain in children.